Mechanistic perspective and functional activity of insulin in amylin aggregation - Baram, Michal (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
Insulin is a key regulatory polypeptide that is secreted from pancreatic β-cells and has several important effects on the synthesis of lipids, regulation of enzymatic activities, blood glucose levels and the prevention of hyperglycemia. Insulin was demonstrated to self-assemble into ordered amyloid fibrils upon repeated injections, although the possible biological significance of the supramolecular structures is enigmatic. Amylin is also an amyloidogenic polypeptide that is secreted from pancreatic β-cells and plays an important role in glycemic regulation preventing post-prandial spikes in blood glucose levels. These two amyloidogenic proteins are secreted together from the pancreas and have the ability to interact and produce insulin–amylin aggregates. So far, the molecular architecture of insulin–amylin complexes at the atomic resolution has been unknown. The current work identifies for the first time the specific π–π interactions between Y16 in insulin and F19 in amylin that contribute to the stability of the insulin–amylin complex, by using experimental and molecular modeling techniques. We performed additional experiments that verify the functional activity of insulin in amylin aggregation. Our findings illustrate for the first time the specific interactions between insulin and amylin aggregates at the atomic resolution and provide a new mechanistic perspective on the effect of insulin on amylin aggregation and may pave the way towards pharmacological intervention in this process.